PENGARUH KEPEMIMPINAN DAN KONFLIK INTERNAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT TRI BAKTI SARIMAS KAB KUANTAN SINGINGI - Irfanul Hakim; Dewita Suryati Ningsih; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at PT. Tri Bakti Sarimas which have address of Kecamatan Pucuk Rantau Kabupaten Kuantan Singingi. Amount of sampel in this research was counted 90 people or totalize the overall of population. Intake of sampel relied on census method. As the result of calculation of band analysis known that no influence which was signifikan between leadership to employees productivity, while internal conflict have an effect on to work productivity.As the result of indirect influence analysis of leadership to work productivity through internal conflict have influence of signifikan to work productivity at PT. Tri Bakti Sarimas Kecamatan Pucuk Rantau Kabupaten Kuantan Singingi. Equally leadership of its influence strength will be more work productivity through processing of internal conflict.As the result of calculation of coefficient of determinasi, obtained by value of R Square equal to 0.243, hence that contribution influence of independent variable to variable of dependen equal to 24.3 %. While the rest 74,7 % influenced by other variable which do not be packed into model of regresi.Keywords: Work Productivity, Leadership, Internal Conflict